Neuroprotective and Antiamnesic Effects of Mitragyna inermis Willd (Rubiaceae) on Scopolamine-Induced Memory Impairment in Mice - Pahaye, David Bougolla (Behav Neurol, 2017)
Aim. To assess memory improvement and neuroprotective and antioxidant effects of Mitragyna inermis (M. inermis) leaf decoction on the central nervous system. Methodology. Leaf decoction of M. inermis was tested on learning and memory in normal and scopolamine-induced cognitive impairment in mice using memory behavioral tests such as the Morris water maze, object recognition task, and elevated plus maze. Oxidative stress enzymes—catalase, superoxide dismutase, and the thiobarbituric acid reactive substance, a product of lipid peroxidation—were quantified. In each test, mice 18 to 25 g were divided into groups of 5. Results. The extract reversed the effects of scopolamine in mice. The extract significantly increased discrimination index in the object recognition task test and inflexion ratio in the elevated plus maze test. The times spent in target quadrant in MWM increased while the transfer latency decreased in mice treated by M. inermis at the dose of 196.5 mg/kg. The activity levels of superoxide dismutase and catalase were significantly increased, whereas the thiobarbituric acid reactive substance was significantly decreased after 8 consecutive days of treatment with M. inermis at the dose of 393 mg/kg. Conclusion. These results suggest that M. inermis leaf extract possess potential antiamnesic effects.